2011
DOI: 10.1074/jbc.m111.258707
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase SMAD Ubiquitination Regulatory Factor 2 Negatively Regulates Krüppel-like Factor 5 Protein

Abstract: Background:The pro-proliferative Krüppel-like factor 5 (KLF5) is posttranslationally regulated. Results: SMAD ubiquitination regulatory factor 2 (SMURF2) interacts with, ubiquitinates and degrades KLF5. Conclusion: SMURF2 negatively regulates KLF5. Significance: The findings increase the understanding of the mechanisms by which KLF5 is regulated posttranslationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…A previous study showed that the E3 ubiquitin ligase WWP1 inhibits KLF2 transcriptional activity and targets KLF2 for ubiquitination and degradation in a ubiquitin ligase activity independent manner [23]. The E3 ubiquitin ligase Smurf1can target KLF2 for degradation in H1299 cells [29]. Our data showed that KLF2 protein expression levels increased when HRECs and HUVECs were infected with AX2R lentivirus.…”
Section: Discussionsupporting
confidence: 54%
“…A previous study showed that the E3 ubiquitin ligase WWP1 inhibits KLF2 transcriptional activity and targets KLF2 for ubiquitination and degradation in a ubiquitin ligase activity independent manner [23]. The E3 ubiquitin ligase Smurf1can target KLF2 for degradation in H1299 cells [29]. Our data showed that KLF2 protein expression levels increased when HRECs and HUVECs were infected with AX2R lentivirus.…”
Section: Discussionsupporting
confidence: 54%
“…Steady-state levels can be reduced by affecting any level of gene expression including inhibiting its transcription or translation, or by increasing its rate of degradation. Serving as clear examples of the latter, overexpression of the mammalian ubiquitin E3 ligase MKRN1 results in the degradation of the hTERT telomerase subunit (Kim et al 2005) and overexpression of the SMURF2 ubiquitin E3 destabilizes the KLF5 DNA-binding protein (Du et al 2011). Consistent with its identification as a specific regulator, knockdown of the SMURF2 E3 ligase increases the level of KLF5.…”
Section: Inhibitionmentioning
confidence: 51%
“…KLF5 has been identified as an unstable protein that is ubiquitinated by WWP1 [17], FBW7 [18], SMURF2 [15] and EFP [16]. KLF5 K369Q could be detached from the proposed E3 ligase constitutively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that KLF5 is an unstable protein with a short half-life [14] and is degraded at least through the ubiquitination-proteasome pathway [14]. WWP1, FBW7, SMURF2 and EFP have been identified as E3 ligases that target KLF5 for ubiquitination and subsequent degradation [1518]. However, whether the acetylation of KLF5 affects its protein stability is unknown at present.…”
Section: Introductionmentioning
confidence: 99%